ANALISIS PENGARUH NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASSETS (ROA) PADA BANK PERKREDITAN RAKYAT DI KALIMANTAN BARAT - B01109083, Khairul Ikhwan Parinduri (Jurnal Pembangunan dan Pemerataan, 2013)
The title of this research is "An Analysis of The effect of Non Performing Loan (NPL) on Return On Assets (ROA) in Rural Bank (BPR) of West Borneo aims to investigate and analyze the influences of Non Performing Loan (NPL) on Return On Assets (ROA) in Bank Perkreditan Rakyat of West Borneo. To examine this relation, the researcher applied the method of simple linear regression which use secondary data taken from Bank Indonesia Publication. Acording to t test in data analyze, the value result 0.502190 was bigger than alpha 0.05. this it indicates that Non Performing Loan (NPL) has a positive effect and not significant to Return On Assets (ROA) in BPR of West Borneo. The Value of R2 accounted for 0.005453, lower than showed than Non Performing Loan (NPL) had a little effect on Return On Assets (ROA). Keywords: Non Performing Loan (NPL), Return ON Assets (ROA), BPR